Lags in transmission of inflation - Bradley, John (Economic & Social Studies, 1977)
In the July 1976 issue of The Economic and Social Review, P. T. Geary presented some preliminary results on the analysis of lags in the transmission of inflation. Essentially his paper consisted of the following points. (a) An examination of six simple bivariate relationships connecting the percentage rates of change of the Irish CPI (Consumer Price Index), WPI (Wholesale Price Index), PX (Export Unit Value Index), PM (Import Unit Value Index), and the UK RPI (Retail Price Index). (b) The use o f the Almon lag procedure to estimate polynomial lags of order four and of lengths varying from four to eight quarters. (c) An economic rationalisation of the bimodal nature of the lags estimated in terms of the distinction between consumer and capital goods.
Keywords: Inflation; Ireland